Unveiling the Mechanism of Deprotonation and Proton Transfer of DNA Polymerase Catalysis via Single‐Molecule Conductance - Lihua Zhao; Yang Xu; Zhiheng Yang; Wenzhe Liu; Shichao Zhong; Jingwei Bai; Xuefeng Guo (Advanced Science)
Abstract DNA polymerases (Pols) play important roles in the transmission of genetic information. Although the function and (de)regulation of Pols are linked to many human diseases, the key mechanism of 3′‐OH deprotonation and the PPi formation are not totally clear. In this work, a method is presented to detect the full catalytic cycle of human Pol (hPol β) in graphene‐molecule‐graphene single‐molecule junctions. Real‐time in situ monitoring successfully revealed the spatial and temporal properties of the open and closed conformation states of hPol β, distinguishing the reaction states in the Pols catalytic cycle and unveiling 3′‐OH deprotonation and pyrophosphate (PPi) formation mechanism of hPol β. Proton inventory experiment demonstrated that the rate‐limiting step of PPi formation is deprotonation, which occurs before a reverse conformational change. Additionally, by detecting the acidity (pKa), it is found that MgA‐bound OH− acted as a general base and activated the nucleophile of 3′‐OH, and that acidic residue D190 or D192 coordinated with MgB as a proton donor to PPi. This work provides useful insights into a fundamental chemical reaction that impacts genome synthesis efficiency and Pol fidelity, which the discovery of Pol‐targeting drugs and design of artificial Pols for DNA synthetic applications are expected to accelerated.